2022
DOI: 10.3389/fmicb.2022.838836
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Ochrobactrum sp. on Biochar/Clay Composite Particle: Optimization of Preparation and Performance for Nitrogen Removal

Abstract: The objective of this study was to prepare biochar/clay composite particle (BCCP) as carrier to immobilize Ochrobactrum sp. to degrade ammonia nitrogen (NH4+-N), and the effects of calcined program and immobilizing material were investigated. Results reflected that the parameters were as follows: calcined temperature 400°C, heating rate 20°C min–1, and holding time 2 h, and the adsorption capacity could reach 0.492 mg g–1. Sodium alginate/polyvinyl alcohol, as embedding material, jointed with NH4+-N adsorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…However, the effect of the P-B-SA + PVA group is lower than that of the P-B group after a period of time, and then the removal efficiency of the P-B-SA + PVA group restored and equivalented to the P-B group with the further extension of the reaction time. It indicated that the embedding first had a certain inhibitory effect on the experiment, and then the permeability became stronger, and the degradation effect was significantly improved with the increase in enrichment [6]. The results showed that BCCP could improve the degradation efficiency of NH 4 + -N as the carrier of immobilized AOB.…”
Section: Performances Of Individual Aob and Petroleum-degrading Bacte...mentioning
confidence: 92%
See 2 more Smart Citations
“…However, the effect of the P-B-SA + PVA group is lower than that of the P-B group after a period of time, and then the removal efficiency of the P-B-SA + PVA group restored and equivalented to the P-B group with the further extension of the reaction time. It indicated that the embedding first had a certain inhibitory effect on the experiment, and then the permeability became stronger, and the degradation effect was significantly improved with the increase in enrichment [6]. The results showed that BCCP could improve the degradation efficiency of NH 4 + -N as the carrier of immobilized AOB.…”
Section: Performances Of Individual Aob and Petroleum-degrading Bacte...mentioning
confidence: 92%
“…However, the use of high-efficiency bacterial agents is affected by the persistence of residence in freely flowing water bodies. Using BCCP as a carrier to immobilize efficient bacterial communities on BCCP can effectively maintain the concentration of microorganisms and provide pollutant degradation effects [6]. Meanwhile, environmental factors, such as salinity and temperature, restrict pollutant degradation, and it is necessary to study the degradation of pollutants by immobilized bacteria technology in wetlands [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation